ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGOBATAN PENDERITA DIABETES MELITUS - Zaenab M. Syahid; Juminten Saimin; Asnia Zainuddin (NHM PRESS, 2021)
The general purpose of this study was to analyze the factors related to medication adherence of patients with diabetes mellitus in the working area of ​​the Rumbia Public Health Center, Bombana Regency. This research is an analytical survey research using a cross sectional design. The population in this study were all patients diagnosed with diabetes mellitus who were on an outpatient basis and registered/ domiciled in the working area of ​​the Rumbia Health Center, namely 196 people. The number of samples in this study were 85 people. The results of testing factors related to medication adherence of people with diabetes mellitus in the working area of ​​the Rumbia Health Center are as follows: There is a relationship between medication adherence of people with diabetes mellitus with knowledge (ρ = 0.000), attitude (ρ = 0.012), motivation (ρ = 0.000), family support (ρ = 0.000), support from health workers (ρ = 0.000), and the most dominant variable related to medication adherence of people with diabetes mellitus in the working area of ​​the Rumbia Public Health Center, Bombana Regency, was family support with Exp(B) or OR= 82,352 and the value of is 0.008. so it is recommended to further improve the prevention of complications by increasing patient compliance. For further researchers, this research is a contribution of thought which is expected to be used as reference material for other researchers who want to develop methods and studies related to diabetes mellitus.